Analgesic Effect of Ageratina adenophora Ethanol Extract on Migraine Rat Model - Hongmin Wang, Peng Guo, Xiang Li, Mei Xu, Yue Xing, Chunyan Li, Yunpeng Luan, Li Zheng (Forest Chemicals Review, 2021)
This study explored the effect of ethanol extract of Ageratina adenophora on migraine caused by nitroglycerin and its mechanism. The rats were pretreated with ethanol extract of Ageratina adenophora (dose: 21.05g/kgbw), and the rats were pretreated by intragastric administration for 7 days. After the last administration, 30 minutes, the rats were induced with nitroglycerin (dose: 10mg/kg). Headache symptoms. Detect the behavioral indicators of rats by recording the times of scratching their heads and climbing their cages, and determine the levels of nitric oxide (NO) in serum of rats by enzyme-linked immunosorbent assay; and the content of calcitonin gene-related peptide (CGRP) and endothelin (ET) in plasma and the content of serotonin (5-HT) and norepinephrine (NE) in the brainstem. The results showed that the ethanol extract of Ageratina adenophora significantly reduced the number of head scratching and cage climbing in migraine rats (P<0.01), and significantly reduced the levels of NO (P<0.05) in serum and CGRP and ET in plasma (P<0.01). Increase the content of 5-HT and NE in the brainstem of rats (P<0.01). Conclusion: The ethanol extract of Ageratina adenophora reduces the damage caused by nitroglycerin and protects the migraine rat model.